2018
DOI: 10.21037/atm.2018.04.22
|View full text |Cite
|
Sign up to set email alerts
|

Microglial priming in Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a chronic and progressive neurodegenerative disease of central nervous system (CNS). Nowadays, increasing evidence suggests that immune system plays a significant role in the mechanisms of AD's onset and progression. Microglia, the main participator in the immune system of CNS, is always regarded as a protector of our brain in a healthy state and also has a beneficial role in maintaining the homeostasis of CNS microenvironment. However, chronic and sustained stimulation can push mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 129 publications
(153 reference statements)
2
83
0
Order By: Relevance
“…As PD can prime macrophages either through microbial factors (e.g., lipopolysaccharide) 54 , 55 or by activation of other immune and non-immune cells 56 , 57 , microglia priming, activation, and polarization due to PD may be plausible 24 . The exaggerated response of primed microglia is known to contribute to the pathogenesis of AD 58 . In contrast to our previous study where we reported a significant increase in the level of some inflammatory cytokines (GM-CSF, IL-6, IFN-γ, and IL-1β) in 3-month-old 5xFAD mice 3 , in the current study using 8-month-old 5xFAD mice, these specific cytokines were not increased.…”
Section: Discussionmentioning
confidence: 99%
“…As PD can prime macrophages either through microbial factors (e.g., lipopolysaccharide) 54 , 55 or by activation of other immune and non-immune cells 56 , 57 , microglia priming, activation, and polarization due to PD may be plausible 24 . The exaggerated response of primed microglia is known to contribute to the pathogenesis of AD 58 . In contrast to our previous study where we reported a significant increase in the level of some inflammatory cytokines (GM-CSF, IL-6, IFN-γ, and IL-1β) in 3-month-old 5xFAD mice 3 , in the current study using 8-month-old 5xFAD mice, these specific cytokines were not increased.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia and astrocytes primed by HIV may play important roles in engulfing and purging Aβ plaques from the brain. 46 In severe HAD with a disrupted blood-brain barrier, amyloid clearance may be enhanced in some individuals. Also, in treated PLHIV, amyloid clearance may occur through HIV-1 Tat priming and activation of microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation plays a key role in the etio-pathogenesis of Alzheimer's disease and other neurodegenerative disorders (Edison et al, 2008;Fernandez-Botran et al, 2011;Fan et al, 2015b;Stefaniak and O'Brien, 2016). Pre-clinical models (Heppner et al, 2015;Hoeijmakers et al, 2016;Villegas-Llerena et al, 2016;Li et al, 2018;Wang et al, 2018), and research in humans (Fernandez-Botran et al, 2011;Edison et al, 2013;Fan et al, 2015b;Stefaniak and O'Brien, 2016), demonstrate that microglia of the brain's innate immune system are activated in Alzheimer's and related diseases. In addition, genetic association studies have demonstrated a link between Alzheimer's disease and polymorphisms and mutations of genes linked to immune responses (Villegas-Llerena et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms and mediators of inflammatory risk in Alzheimer's disease are not fully understood, synaptic and neuronal injury may arise from the release of cytokines and pro-inflammatory molecules such as interleukin-1ß and TGF-ß (Fernandez-Botran et al, 2011), or direct microglial injury to synapses . These, in turn, impair synaptic function, network communication, and may accelerate neurodegeneration and synaptic loss (Heppner et al, 2015;Hoeijmakers et al, 2016;Villegas-Llerena et al, 2016;Li et al, 2018;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%